2011
DOI: 10.1002/hep.24172
|View full text |Cite
|
Sign up to set email alerts
|

Genotype differences in susceptibility and resistance development of hepatitis C virus to protease inhibitors telaprevir (VX-950) and danoprevir (ITMN-191)

Abstract: Protease inhibitors (PIs) have proven to be effective adjuncts to interferon/ribavirin treatment of hepatitis C virus (HCV) infections. Little clinical or in vitro data exists, however, on their effectiveness for nontype 1 genotypes that predominate in Europe, the Middle East, Africa, and most of Asia. NS3 protease and NS4A genes from genotypes 1-6 were inserted into the JFH clone to generate replication-competent intergenotype chimeras. Susceptibility to PIs was determined by replication and infectivity assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 39 publications
(70 reference statements)
7
58
0
Order By: Relevance
“…Our results here also showed that all the in vitro-synthesized proteases derived from HCV subtype 2a samples were less susceptible to telaprevir than the proteases derived from HCV subtype 1b samples, which is consistent with a previous finding (22). The power of the in vitro-synthesized protease assay to differentiate the resistance levels between HCV genotype 2 and HCV genotype 1 may indicate that the in vitro-synthesized protease assay is applicable for testing resistance variants in clinical sera.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results here also showed that all the in vitro-synthesized proteases derived from HCV subtype 2a samples were less susceptible to telaprevir than the proteases derived from HCV subtype 1b samples, which is consistent with a previous finding (22). The power of the in vitro-synthesized protease assay to differentiate the resistance levels between HCV genotype 2 and HCV genotype 1 may indicate that the in vitro-synthesized protease assay is applicable for testing resistance variants in clinical sera.…”
Section: Discussionsupporting
confidence: 92%
“…Major differences have been found between HCV genotypes in their susceptibilities and resistance development to telaprevir (22,23). Our results here also showed that all the in vitro-synthesized proteases derived from HCV subtype 2a samples were less susceptible to telaprevir than the proteases derived from HCV subtype 1b samples, which is consistent with a previous finding (22).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, genotyping for HCV-1 subtypes will not impact on the day-to-day clinical management of chronic HCV infection, whereas conflicting reports exist on their influence on the outcome following conventional therapy with Peg-IFN and RIBA (6)(7)(8)(9)(10)(11)(12)(13). Recently, several HCV inhibitors appear to have selective activity against HCV 1 subtypes both in vitro and in vivo, with subtype 1a appearing more resistance-prone and less responsive to triple therapy than subtype 1b (25)(26)(27)(28)). …”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, liver fibrosis was not a predictor in both subtypes. Interestingly, a robust reverse association with biological plausibility has been observed with the new HCV-targeted protease inhibitors (PIs), with subtype 1a appearing more resistance-prone and less responsive to triple therapy than subtype 1b [14]. A similar observation has been noticed with genotype 3, which appears to be less susceptible to the first generation of DAA PIs, telaprevir and boceprevir, and also to polymerase inhibitors including sofosbuvir [15].…”
mentioning
confidence: 86%